Model Transparansi Pengelolaan Dana Desa untuk Mewujudkan Pembangunan Berkelanjutan di Indonesia - Susniwati Susi; Diana Sukorina; Yulinda Uang (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2026)
Village fund transparency is widely recognized as a prerequisite for ensuring public accountability and fostering sustainable development in Indonesia. Despite the existence of formal regulations, challenges remain at the implementation level, particularly in relation to limited digital literacy, insufficient community involvement, and weak administrative capacity within village institutions. This study aims to formulate an adaptive and context-specific model of village fund transparency that not only complies with regulatory frameworks but also incorporates local cultural values to strengthen governance legitimacy. A qualitative multiple-case study design was applied in selected villages in Central Java and South Sulawesi. Data collection involved in-depth interviews, focus group discussions (FGDs), and the examination of official documents. Thematic content analysis was employed to identify emerging patterns, while data validity was ensured through triangulation of sources, methods, and member checking with informants. The study identified three fundamental pillars of effective transparency: (1) digital-based information disclosure to enhance public access, (2) inclusive community participation in both planning and monitoring processes, and (3) the integration of local cultural norms into governance mechanisms. This framework addresses the shortcomings of rigid and formalistic systems and contributes to stronger social legitimacy in village governance.The research offers theoretical insights into the discourse on public administration, particularly regarding fiscal transparency at the village level. Practically, the proposed model provides a framework for policymakers to design village fund governance strategies that are more adaptive, participatory, and sustainable in the long term.